2016
DOI: 10.1111/jch.12893
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Resolving Hyperreninemic Hypertension Caused by Accessory Renal Artery Stenosis in a 13‐Year‐Old Girl: A Case Report

Abstract: The authors describe the clinical investigation and progress of a 13-year-old girl diagnosed with hypertension 4 years prior to her admission. A thorough history was taken and physical examination performed. Laboratory analysis and relevant radiological evaluation were obtained in order to determine the etiology for suspected secondary hypertension, and later to differentiate between the possible causes of hyperreninemic hypertension. The patient had an accessory left renal artery, presumptively leading to ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…Akbeyaz et al describe a case of a 13-year-old female with hypertension secondary to stenosis of an accessory renal artery identified on renal ultrasound and confirmed on CT angiography [ 7 ]. The patient received antihypertensive pharmacologic treatment and blood pressure goal was achieved [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Akbeyaz et al describe a case of a 13-year-old female with hypertension secondary to stenosis of an accessory renal artery identified on renal ultrasound and confirmed on CT angiography [ 7 ]. The patient received antihypertensive pharmacologic treatment and blood pressure goal was achieved [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…At routine follow-up two months later, it was discovered that the patient's blood pressure was much lower than previous measurements and antihypertensive treatment was gradually tapered and discontinued [7]. Repeat renal ultrasound was performed and the accessory artery could no longer be visualized [7]. Spontaneous collapse of the vessel was suspected [7].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Also, several cases of renovascular hypertension and renal artery stenosis in MPNs patients have been described . However, in spite of recent progress in the diagnosis and treatment strategy of renovascular hypertension and renal artery stenosis, the common clinical manifestations of patients with MPN‐associated renovascular hypertension are unclear and optimal treatment strategy for the renovascular lesion in such patients are undetermined.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] Also, several cases of renovascular hypertension and renal artery stenosis in MPNs patients have been described. [11][12][13][14][15][16] However, in spite of recent progress in the diagnosis and treatment strategy of renovascular hypertension and renal artery stenosis, [17][18][19] the common clinical manifestations of patients with MPN-associated renovascular hypertension are unclear and optimal treatment strategy for the renovascular lesion in such patients are undetermined. the authors showed that the stenotic lesions in the renal arteries were radiographically considered to be thrombotic plaque or intimal hyperplasia, which would be associated with PV and ET.…”
mentioning
confidence: 99%